Inelastic electron tunneling spectroscopy of difurylethene-based photochromic single-molecule junctions - Kim, Youngsang; Bahoosh, Safa G.; Sysoiev, Dmytro; Huhn, Thomas; Pauly, Fabian; Scheer, Elke (Beilstein Journal of Nanotechnology, 2017)
Diarylethene-derived molecules alter their electronic structure upon transformation between the open and closed forms of the diarylethene core, when exposed to ultraviolet (UV) or visible light. This transformation results in a significant variation of electrical conductance and vibrational properties of corresponding molecular junctions. We report here a combined experimental and theoretical analysis of charge transport through diarylethene-derived single-molecule devices, which are created using the mechanically controlled break-junction technique. Inelastic electron tunneling (IET) spectroscopy measurements performed at 4.2 K are compared with first-principles calculations in the two distinct forms of diarylethenes connected to gold electrodes. The combined approach clearly demonstrates that the IET spectra of single-molecule junctions show specific vibrational features that can be used to identify different isomeric molecular states by transport experiments.
Keywords: inelastic electron tunneling spectroscopy; molecular junction; photochromic; single molecule